"I Am My Body". Physical Selves of Police Officers in a Changing Institution. (22nd August 2016) - Courpasson, David; Monties, Vanessa
ABSTRACT: Most studies on identity work have overlooked the corporeal quality of occupational life. Despite calls to attempt such engagement, little is known about the role of the body in occupations for which corporeal elements are central in the affirmation of identity. This study aims to answer such calls by providing a detailed ethnography of police work. Focusing on four bodily practices, we demonstrate how fitness, intimidation, cleanliness, and toughness are central elements to the officers' construction of self. We thereby highlight the notion of physical selfhood as a way to understand the body/identity nexus among police officers and their capacity to resist new work requirements. We view bodies through a lens of resistance, rather than docility and compliance as much previous research has done. We aim to contribute to scholarship on identity work by portraying the politicization of bodies as a powerful component, thereby helping professionals to deflect some important institutional pressures affecting their work.